Pelatihan Pengembangan Media Videoscribe dengan Konteks Lokal dalam Mengajarkan Objek Matematika bagi MGMPSMAKabupaten Bintan - Febrian Febrian; Puji Astuti; Rindi Antika (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2019)
ABSTRACTThe biggest challenge for Mathematics teachers is mastering Mathematics material with its abstract, logical, systematic and structured character for itself before teaching it to students. The teacher must mastering mathematical objects such as facts, concepts, operations, and principles and be able to describe these objects in every Math material. Not only that, the challenges from the pedagogical aspects also forced teachers to be able to think about how to teach abstract Mathematics material to students so that learning objectives are achieved. The choice of context and learning media is also an important aspect contributing to the success of the teaching and learning process. However, all these aspects are often a problem among teachers, especially at the high school level. Weaknesses in mastering the material as well as weaknesses in pedagogical aspects often arise in teaching mathematics. This certainly raises many ideas that can be discussed so that weaknesses can be minimized. One of them is improving understanding of Mathematics objects and emphasizing the choice of context and learning media. In this Community Service activity, the teacher is introduced to the use of videoscribe to develop media with local context in teaching Mathematics objects. Through this activity a change in understanding of mathematical objects, the roles and functions of health and learning media went better. In addition, participants can run videoscribe to create learning media that integrates all of the above aspects.Keywords: local context, learning media, mathematics object, videoscribe ABSTRAKTantangan terbesar bagi guru Matematika adalah menguasai materi Matematika dengan karakternya yang abstrak, logis, sistematis dan terstruktur untuk dirinya sendiri sebelum mengajarkannya kepada siswa. Guru harus menguasai objek matematika seperti fakta, konsep, operasi, dan prinsip dan mampu menguraikan objek-objek tersebut di setiap materi Matematika. Tak hanya itu, tantangan dari aspek pedagogis juga memaksa guru untuk dapat memikirkan bagaimana cara mengajarkan materi Matematika yang abstrak tersebut kepada siswa agar tujuan pembelajaran tercapai. Pemilihan konteks dan media pembelajaran sekiranya juga menjadi aspek penting penyumbang keberhasilan proses pengajaran dan pembelajaran. Namun, semua aspek-aspek tersebut seringkali menjadi permasalahan di kalangan Guru terutama pada level SMA. Kelemahan penguasaan materi serta kelemahan dalam aspek pedagogis seringkali muncul dalam pengajaran matematika. Hal ini tentunya memunculkan banyak ide yang dapat diperbincangkan agar kelemahan dapat diminimalisir. Salah satunya adalah peningkatan pemahan terhadap objek Matematika serta penekanan pada pemilihan konteks dan media pembelajaran. Dalam kegiatan Pengabdian kepada Masyarakat ini, guru diperkenalkan pada penggunaan videoscribe untuk mengembangkan media dengan konteks lokal dalam mengajarkan objek Matematika. Melalui kegiatan ini terjadi perubahan pemahaman mengenai objek matematika, peran dan fungsi kontkes dan media pembelajaran ke arah lebih baik. Di samping itu, peserta dapat menjalankan videoscribe untk membuat media pembelajaran yang mengitgrasikan kesemua aspek di atas.Kata Kunci: konteks lokal, media pembelajaran, objek matematika, videoscribe